THE TIME OF SYNTHESIS AND THE CONSERVATION OF MITOSIS-RELATED PROTEINS IN CULTURED HUMAN AMNION CELLS - Sisken, Jesse E. (The Rockefeller University Press, 1967)
p-Fluorophenylalanine (PFPA), an analogue of phenylalanine which may be incorporated into proteins, increases the duration of mitosis. In the present experiments, based upon quantitative analyses of time-lapse cinemicrographic films, brief treatments of cells with PFPA are shown to affect the duration of metaphase in only those cells which enter division during or shortly after treatment. The offspring of cells with prolonged metaphases also tend to have prolonged metaphases. Analyses of the kinetics of the appearance of prolonged metaphases indicate that some protein specifically associated with mitosis is synthesized primarily during a period which corresponds closely to G(2). The manner in which the defect is passed on to daughter cells indicates that the protein involved is conserved and reutilized by daughter cells for their subsequent divisions. Comparable experiments performed with low concentrations of puromycin indicate that the major effect of PFPA is due to its incorporation into protein rather than its ability to inhibit protein synthesis. The fact that puromycin-induced effects can also be passed on to daughter cells is interpreted to mean that cells make only specific amounts of some mitosis-associated proteins and that if a cell "inherits" a deficiency in such protein it is not able to compensate for the deficiency.